Towards an Integrated Multi-Omic Approach to Improve the Diagnostic Accuracy of Fine-Needle Aspiration in Thyroid Nodules with Indeterminate Cytology - Monia Bordoni; Nairus Aboud; Francesca Silvetti; Augusto Taccaliti; Giancarlo Balercia; Gianmaria Salvio (Diagnostics, 2025)
Thyroid nodules are accidentally found in up to 68% of people undergoing neck ultrasound (US) examination, and fine needle aspiration (FNA) is the current gold standard to discriminate between malignancy and benign lesions. Unfortunately, one-third of FNAs are classified as indeterminate, requiring surgery for definitive diagnosis. This leads to high costs and health risks of unnecessary procedures, since malignancies are observed in less than half of operative specimens. This narrative review aims to describe the most innovative multi-omics approach techniques, including genomics, proteomics, and metabolomics, aimed at making the preoperative evaluation of indeterminate thyroid nodules more accurate. The advantages and disadvantages of the techniques are described in detail, and a SWOT (strengths, weaknesses, opportunities, and threats) analysis of the multi-omic approach is provided.